P1152Health-related quality of life among implantable cardioverter defibrillator patients compared to age- and sex-matched norms. (18th June 2020) - Magnusson, P; Karlsson, J; Wallhagen, M; Mattsson, G
Abstract: Background The decision to implant an ICD integrates presumed health-related quality of life (HRQL). Purpose To assess HRQL in ICD patients using the questionnaire SF-36, and compare it to a Swedish age- and sex-matched population. Methods SF-36 of ICD patients 2007-2017 (response rate 77.2%) were analysed using the Mann-Whitney U-test and effect size (ES). Results In total, 223 patients (mean age 71.1 ±9.7 years) were included of whom 33.6% had a CRTD. A majority were men 82.1% (n = 183) and 60.1% (n = 134) had an ICD due to primary prevention. SF-36 score are summarized as Table 1. Mean age was similar between men and women (71.1 vs 70.9 years) and there were no significant difference score at any domain, including both component scores. Primary and secondary prevention patients (mean age 70.3 vs 72.3 years) scored similar except for worse GH in PP (p = 0.016, ES 0.35). A history of atrial fibrillation at baseline was associated with worse PF (ES 0.41) and PCS (ES 0.38). Neither appropriate therapy, inappropriate shock, nor complications requiring surgery, were associated with lower scores in any domain. In primary prevention due to ischemic vs non-ischemic cardiomyopathy no domain were significantly different. PCS decreased with higher age strata (p = 0.002) in contrast to MCS (p = 0.986). Conclusion Patients with ICDs have lower physical and mental HRQL than age- and sex matched norms; however the effect sizes are small. HRQL is similar regardless of sex, primary vs secondary prevention indication, appropriate therapy, inappropriate shock or complications but decreases with age.